0
$\begingroup$

My goal is to find the Fourier transform of the following functions.

$$y_1(t) = (t-2)e^{-t} u(t-2)$$ $$y_2(t) = y_1(t)\times \cos(2\pi mt)$$ $$y_3(t) =y_2(t)\times A\cos (2\pi mt +\phi))$$

$m$, $A$ and $\phi$ are just unknowns.

I have found:

$\mathcal{F}\{y_1(t)\} = \frac{e^{-2(1+j2\pi f)} }{(1+j2\pi f)^2}$
$\mathcal{F}\{\cos(2\pi mt)\} = \frac{1}{2}[\delta(f-m)+\delta(f+m))]$

I am aware of the modulation property of the Fourier transform, so I believe I need to use the Convolution Theorem. However, I am unsure how to sub these transforms into the convolution formula and solve further.

| cite | improve this question | | | | |
$\endgroup$
0
$\begingroup$

Let $\mathcal{F}\{y_1(t)\}=Y_1(f)$ Then using the convolution theorem, $$\mathcal{F}\{y_2(t)\}=Y_2(f)=\frac{1}{2}\left(Y_1(f-m)+Y_1(f+m)\right)$$ and assuming$$\mathcal{F}\{\cos(2\pi mt+\phi)\}=\frac{1}{2}\left(e^{j\phi}\delta(f-m)+e^{-j\phi}\delta(f+m)\right)$$ we have $$\mathcal{F}\{y_3(t)\}=Y_3(f)=\frac{A}{2}\left(e^{j\phi}Y_2(f-m)+e^{-j\phi}Y_2(f+m)\right)$$

This is generally due to the shifting property of delta function: $\delta(f\pm f_0)*F(f)=F(f\pm f_0)$

| cite | improve this answer | | | | |
$\endgroup$
  • $\begingroup$ Thanks a lot for this! Wouldn't the transform of y3 be Y2(f-m)... not Y1(f-m).. Or am I mistaken? $\endgroup$ – tinefihu Sep 21 '16 at 15:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.